Joint Use of Liability and Regulation in Environmental Law - Stephan Michel; Alessandro Romano; Ugo Zannini (University of Hamburg, Institute of Law and Economics (ILE), 2017)
In this paper, we argue that the joint use of ex-ante regulation and ex-post liability rules is efficient when there are uncertainty surrounding causal investigations and regulatory myopia. As these conditions are generally met in environmental cases, we provide an explanation for the frequent coexistence of these two instruments to control activities that create a risk for the environment. Moreover, we suggest that a joint use of liability and regulation should more frequently be optimal at the European (Federal) level than at the Country (State) level.
Keywords: K13; K32; L50; Q52; Q58; 330; Regulation; Liability; Joint Use; Causal Uncertainty; Regulatory Myopia; Precautionary Principle